Wear-resistant and high-comfort plastic boot for industry and mining
The problem of insufficient wear resistance and comfort of the industrial and mining boot lining is solved by using modified silica spinning liquid prepared by electrospinning and ultraviolet irradiation treatment. It achieves higher wear resistance and hygroscopicity, extends service life and reduces odor feet problems.
Patent Information
- Application Number
- CN202411592643.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-01-07
AI Technical Summary
The lining of existing industrial and mining boots is not wear-resistant and comfortable, easy to damage, and poor moisture absorption and breathability, resulting in wear problems of odor, rotten feet and soles.
Using injection molded PVC boots combined with wear-resistant and moisture-absorbing non-woven lining, the modified silica spinning liquid is prepared by electrospinning and roller hot rolling, which increases the dispersion and antibacterial properties of the spinning liquid, and passes through ultraviolet The light irradiation is grafted to form a wear-resistant and hygroscopic non-woven liner.
It improves the wear resistance and hygroscopicity of industrial and mining boots, reduces foot sweat accumulation and bacterial growth, extends service life and improves comfort.
Smart Images

Figure BDA0005125984250000031 
Figure BDA0005125984250000041 
Figure BDA0005125984250000111
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of plastic boot preparation, and in particular relates to a wear-resistant and highly comfortable plastic boot for industrial and mining use. Background Art
[0002] Mining boots are a type of labor protection shoes. The outsole has a coarse and deep pattern, is non-slip and wear-resistant, and is suitable for mining workers to wear rubber protective boots. The lining of existing mining boots is usually made of ordinary fabrics, which has poor wear resistance and low comfort. In addition, the surrounding environment of the mine is relatively complex. Mining workers wearing mining boots need to experience many footsteps, which can easily cause damage to the lining of mining boots. In addition, the existing mining boots have poor moisture absorption and air permeability. Wearing them for a long time will cause smelly feet, rotten feet, and wear and blistering of the soles of the feet. Therefore, providing a wear-resistant and highly comfortable mining plastic boot is a technical problem that needs to be solved at present. Summary of the invention
[0003] The object of the present invention is to provide a wear-resistant and highly comfortable plastic boot for industrial and mining use, so as to solve the problems raised in the above-mentioned background technology.
[0004] The purpose of the present invention can be achieved through the following technical solutions:
[0005] A wear-resistant and highly comfortable plastic boot for industrial and mining use, comprising an injection-molded PVC boot and a wear-resistant, moisture-absorbing non-woven fabric lining;
[0006] The wear-resistant and highly comfortable industrial and mining plastic boots are made by the following steps:
[0007] Polyurethane adhesive is applied to the inside of the injection-molded PVC boots, and then the wear-resistant and moisture-absorbing non-woven fabric lining is bonded to the inside of the PVC boots. The boots are left standing at room temperature for 4-6 hours to obtain wear-resistant and highly comfortable industrial and mining plastic boots.
[0008] Furthermore, the wear-resistant moisture-absorbing non-woven fabric lining is made by the following steps:
[0009] Step A1, adding high-density polyethylene into a reaction kettle, heating to 120°C, keeping the temperature for 10 minutes, adding difluorochloromethane and modified silica, stirring and heating to 140°C, introducing nitrogen and pressurizing to 6MPa, and at the same time heating to 220°C, stirring at a speed of 80r / min for 1.5h to obtain a spinning solution;
[0010] Step A2, electrospinning the spinning solution obtained in step A1 to obtain a fiber web, and preliminarily hot-rolling the fiber web with a roller to obtain a non-woven fabric; wherein the spinning voltage is 26 kV, the spinning push speed is 0.003 mm / s, and the receiving distance is 6 cm;
[0011] Step A3, xylene ketone and acetone are mixed uniformly in a mass ratio of 1:100 to obtain an initiator solution, the non-woven fabric obtained in step A2 is soaked in the initiator solution for 20 minutes and then taken out, placed in dark conditions for 30 minutes, the modification liquid is sprayed on the non-woven fabric, and then irradiated under an ultraviolet lamp with a power of 400 W and an irradiation spectrum of 380 nm for 5-10 minutes. After the end, ultrasonic cleaning is performed with acetone for 5 minutes, and the cleaning is performed three times. Finally, vacuum drying is performed at 30°C to constant weight, and shearing is performed to obtain a wear-resistant and moisture-absorbing non-woven fabric lining.
[0012] Furthermore, in step A1, the mass ratio of high-density polyethylene, difluorochloromethane and modified silicon dioxide is 4:3:1.
[0013] Furthermore, in step A3, the usage ratio of the modified liquid and the non-woven fabric is 3-5 mL: 25-28 g.
[0014] Further, the modified silicon dioxide in step A1 is prepared by the following steps:
[0015] Step S1, under nitrogen protection, N, N'-dimethyldodecyl tertiary amine, γ-chloropropyltrimethoxysilane and methanol are added to a round-bottom flask, stirred at a speed of 60-80 r / min for 20 min, potassium iodide is added, the reaction temperature is controlled to 70°C, and the reaction is stirred at a speed of 100-200 r / min for 24 h. After the reaction is completed, the reaction product is evaporated under reduced pressure to remove methanol to obtain a viscous product, and the viscous product is dissolved in a solvent mixed with acetone and ethanol in a volume ratio of 1:1 for recrystallization, and filtered to obtain an intermediate product;
[0016] The reaction process is as follows:
[0017]
[0018] Step S2, adding methanol, deionized water and the intermediate product into a round-bottom flask, stirring for 5-8 minutes, adding acetic acid into the round-bottom flask to adjust the pH value to 3-4, hydrolyzing at room temperature for 4 hours, adding nano-silicon dioxide into the round-bottom flask, heating to 110°C, ultrasonically dispersing at a frequency of 48-53kHz for 30 minutes, centrifuging at a speed of 1000-1500r / min for 10 minutes, washing the precipitate with deionized water for 3-5 times, and drying at 110°C to constant weight to obtain modified silicon dioxide.
[0019] Furthermore, in step S1, the usage ratio of N,N'-dimethyldodecyl tertiary amine, γ-chloropropyltrimethoxysilane, methanol and potassium iodide is 0.1 mol: 0.1 mol: 20-35 mL: 0.64-0.83 g.
[0020] Furthermore, in step S2, the mass ratio of methanol, deionized water, intermediate product and nano-silicon dioxide is 7:2:1:9.8-11.2.
[0021] Further, the modified liquid in step A3 is prepared by the following steps:
[0022] Step C1, adding 2-vinyl-4,4-dimethyl-2-oxazolin-5-one, acetone, deionized water and trimethylammonium chloride acetylohydrazide into a reaction kettle, stirring for 5-8 min at a speed of 60-80 r / min, then adding saturated sodium bicarbonate solution, reacting at 37° C. for 24 h, after the reaction is completed, rotary evaporation at 40° C. for 20-30 min, adding 20% sodium chloride solution by mass for salting out, then filtering, and drying the filter cake at 45° C. to constant weight to obtain intermediate 1;
[0023] The reaction process is as follows:
[0024]
[0025] Step C2, add intermediate 1, sodium styrene sulfonate, anhydrous ethanol and deionized water into a stirring tank, stir evenly at a speed of 100-200 r / min to obtain a modified liquid.
[0026] Furthermore, in step C1, the dosage ratio of 2-vinyl-4,4-dimethyl-2-oxazolin-5-one, acetone, deionized water, trimethylammonium chloride acetohydrazide, and saturated sodium bicarbonate solution is 0.1 mol: 35-41 mL: 40-45 mL: 0.1 mol: 16-22 mL.
[0027] Furthermore, in step C2, the usage ratio of intermediate 1, sodium styrene sulfonate, anhydrous ethanol and deionized water is 1.5-2.4 g: 2.8-4.3 g: 45-48 mL: 30 mL.
[0028] Beneficial effects of the present invention:
[0029] The invention improves the comfort and durability of workers by changing the inner lining cloth of traditional PVC plastic boots for industrial and mining use. Firstly, N, N'-dimethyl dodecyl tertiary amine and γ-chloropropyl trimethoxy silane are used as raw materials, and an intermediate product containing an alkyl long chain, a quaternary ammonium salt structure and a -SiO-CH3 structure is obtained through a chemical reaction. Then, the intermediate product is hydrolyzed in a methanol aqueous solution to hydrolyze -SiO-CH3 into -SiO-CH3. i-OH, and then undergo a dehydration condensation reaction with the hydroxyl group on the surface of nano-silica to obtain modified silica. The longer alkyl carbon chain improves the dispersibility of nano-silica in the spinning solution, and the quaternary ammonium salt structure gives the modified silica excellent antibacterial properties. High-density polyethylene, difluorochloromethane and modified silica are used as raw materials, and non-woven fabrics are obtained by electrospinning and roller hot rolling. The modified silica has the characteristics of high hardness and good stability. The alkyl carbon chain on the modified silica can be entangled with high-density polyethylene. The de-entanglement shape during the impact of the material will absorb the impact stress, thereby improving the toughness of the non-woven fabric. As a rigid material, the modified silica can effectively absorb the shear stress caused by friction when the non-woven fabric is rubbed, making the polyethylene difficult to slip, thereby reducing the friction loss quality and increasing the wear resistance of the non-woven fabric. The non-woven fabric is soaked with a hair dryer, and then the modified liquid is grafted by ultraviolet light to obtain a wear-resistant and hygroscopic non-woven fabric. The intermediate product in the modified liquid is obtained by a ring-opening reaction between 2-vinyl-4,4-dimethyl-2-oxazolin-5-one and trimethylammonium chloride acetylohydrazide, and is grafted on the non-woven fabric with sodium styrene sulfonate under ultraviolet light. The intermediate product contains a halogenamine structure, and oxidative chloride ions contact receptors on bacteria to react quickly to inactivate biological enzymes, thereby causing bacterial apoptosis. The boots have excellent antibacterial properties, and sodium styrene sulfonate has high hydrophilic hygroscopic properties. Therefore, the industrial and mining plastic boots prepared by the wear-resistant and hygroscopic non-woven fabric of the present invention have excellent antibacterial properties, and also have wear-resistant and hygroscopic properties, can absorb foot sweat discharged by workers, reduce the generation of bacteria and odor, and increase the comfort of workers. DETAILED DESCRIPTION
[0030] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] Example 1
[0032] The wear-resistant and moisture-absorbing nonwoven lining is made by the following steps:
[0033] Step A1, add 40g high-density polyethylene into a reaction kettle, heat it to 120°C, keep it warm for 10min, then add 30g difluorochloromethane and 10g modified silica, stir and heat it to 140°C, introduce nitrogen and pressurize it to 6MPa, heat it to 220°C, rotate at 80r / min and stir for 1.5h to obtain a spinning solution;
[0034] Step A2, electrospinning the spinning solution obtained in step A1 to obtain a fiber web, and preliminarily hot-rolling the fiber web with a roller to obtain a non-woven fabric; wherein the spinning voltage is 26 kV, the spinning push speed is 0.003 mm / s, and the receiving distance is 6 cm;
[0035] Step A3, xylene ketone and acetone are mixed uniformly in a mass ratio of 1:100 to obtain an initiator solution, the non-woven fabric obtained in step A2 is soaked in the initiator solution for 20 minutes and then taken out, placed in dark conditions for 30 minutes, the modification liquid is sprayed on the non-woven fabric, and then irradiated under an ultraviolet lamp with a power of 400W and an irradiation spectrum of 380nm for 5-10 minutes. After the end, ultrasonic cleaning with acetone for 5 minutes, cleaning three times, and finally vacuum drying at 30°C to constant weight, shearing and forming, to obtain a wear-resistant and moisture-absorbing non-woven fabric lining; the amount ratio of the modification liquid to the non-woven fabric is 3mL:25g.
[0036] Wherein, the modified silicon dioxide in step A1 is prepared by the following steps:
[0037] Step S1, under nitrogen protection, 0.1 mol of N, N'-dimethyldodecyl tertiary amine, 0.1 mol of γ-chloropropyltrimethoxysilane and 20 mL of methanol were added to a round-bottom flask, stirred at a speed of 60 r / min for 20 min, and then 0.64 g of potassium iodide was added. The reaction temperature was controlled to 70°C, and the reaction was stirred at a speed of 100 r / min for 24 h. After the reaction was completed, the reaction product was evaporated under reduced pressure to remove methanol to obtain a viscous product, and the viscous product was recrystallized in a solvent mixed with acetone and ethanol in a volume ratio of 1:1, and filtered to obtain an intermediate product;
[0038] Step S2, 7g of methanol, 2g of deionized water and 1g of the intermediate product are added to a round-bottom flask, and after stirring for 5min, acetic acid is added to the round-bottom flask to adjust the pH value to 3. After hydrolysis at room temperature for 4h, 9.8g of nano-silicon dioxide is added to the round-bottom flask, the temperature is raised to 110°C, ultrasonically dispersed at a frequency of 48kHz for 30min, and centrifuged at a speed of 1000r / min for 10min. The precipitate is washed three times with deionized water and dried at 110°C to constant weight to obtain modified silicon dioxide.
[0039] Wherein, the modified liquid in step A3 is prepared by the following steps:
[0040] Step C1, 0.1 mol of 2-vinyl-4,4-dimethyl-2-oxazolin-5-one, 35 mL of acetone, 40 mL of deionized water and 0.1 mol of trimethylammonium chloride acetohydrazide were added to a reaction kettle, stirred at a speed of 60 r / min for 5 min, then 16 mL of saturated sodium bicarbonate solution was added, and the reaction was carried out at a temperature of 37° C. for 24 h. After the reaction was completed, rotary evaporation was performed at 40° C. for 20 min, and a 20% sodium chloride solution was added for salting out, and then suction filtration was performed. The filter cake was dried at 45° C. to constant weight to obtain an intermediate 1;
[0041] Step C2, add 1.5 g of intermediate 1, 2.8 g of sodium styrene sulfonate, 45 mL of anhydrous ethanol and 30 mL of deionized water into a stirring tank, stir evenly at a speed of 100 r / min to obtain a modified liquid.
[0042] Example 2
[0043] The wear-resistant and moisture-absorbing nonwoven lining is made by the following steps:
[0044] Step A1, add 40g high-density polyethylene into a reaction kettle, heat it to 120°C, keep it warm for 10min, then add 30g difluorochloromethane and 10g modified silica, stir and heat it to 140°C, introduce nitrogen and pressurize it to 6MPa, heat it to 220°C, rotate at 80r / min and stir for 1.5h to obtain a spinning solution;
[0045] Step A2, electrospinning the spinning solution obtained in step A1 to obtain a fiber web, and preliminarily hot-rolling the fiber web with a roller to obtain a non-woven fabric; wherein the spinning voltage is 26 kV, the spinning push speed is 0.003 mm / s, and the receiving distance is 6 cm;
[0046] Step A3, xylene ketone and acetone are mixed uniformly in a mass ratio of 1:100 to obtain an initiator solution, the non-woven fabric obtained in step A2 is soaked in the initiator solution for 20 minutes and then taken out, placed in dark conditions for 30 minutes, the modification liquid is sprayed on the non-woven fabric, and then irradiated under an ultraviolet lamp with a power of 400 W and an irradiation spectrum of 380 nm for 8 minutes. After the end, ultrasonic cleaning with acetone for 5 minutes, cleaning three times, and finally vacuum drying at 30°C to constant weight, shearing and forming, to obtain a wear-resistant and moisture-absorbing non-woven fabric lining; the amount ratio of the modification liquid to the non-woven fabric is 4mL:27g.
[0047] Wherein, the modified silicon dioxide in step A1 is prepared by the following steps:
[0048] Step S1, under nitrogen protection, 0.1 mol of N, N'-dimethyldodecyl tertiary amine, 0.1 mol of γ-chloropropyltrimethoxysilane and 28 mL of methanol were added to a round-bottom flask, stirred at a speed of 70 r / min for 20 min, and then 0.72 g of potassium iodide was added. The reaction temperature was controlled to 70°C, and the reaction was stirred at a speed of 150 r / min for 24 h. After the reaction was completed, the reaction product was evaporated under reduced pressure to remove methanol to obtain a viscous product, and the viscous product was dissolved in a solvent mixed with acetone and ethanol in a volume ratio of 1:1 for recrystallization, and filtered to obtain an intermediate product;
[0049] Step S2, add 7g methanol, 2g deionized water and 1g intermediate product into a round-bottom flask, stir for 7min, add acetic acid into the round-bottom flask to adjust the pH value to 3, hydrolyze at room temperature for 4h, add 10g nano-silica into the round-bottom flask, heat to 110°C, ultrasonically disperse at a frequency of 50kHz for 30min, centrifuge at a speed of 1200r / min for 10min, wash the precipitate with deionized water 4 times, and dry at 110°C to constant weight to obtain modified silica.
[0050] Wherein, the modified liquid in step A3 is prepared by the following steps:
[0051] Step C1, 0.1 mol of 2-vinyl-4,4-dimethyl-2-oxazolin-5-one, 38 mL of acetone, 42 mL of deionized water and 0.1 mol of trimethylammonium chloride acetohydrazide were added to a reaction kettle, stirred at a speed of 70 r / min for 6 min, then 18 mL of saturated sodium bicarbonate solution was added, and the reaction was carried out at a temperature of 37° C. for 24 h. After the reaction was completed, rotary evaporation was performed at 40° C. for 25 min, and a 20% sodium chloride solution was added for salting out, and then suction filtration was performed. The filter cake was dried at 45° C. to constant weight to obtain an intermediate 1;
[0052] Step C2, add 2.1 g of intermediate 1, 3.2 g of sodium styrene sulfonate, 47 mL of anhydrous ethanol and 30 mL of deionized water into a stirring tank, stir evenly at a speed of 150 r / min to obtain a modified liquid.
[0053] Example 3
[0054] The wear-resistant and moisture-absorbing nonwoven lining is made by the following steps:
[0055] Step A1, add 40g high-density polyethylene into a reaction kettle, heat it to 120°C, keep it warm for 10min, then add 30g difluorochloromethane and 10g modified silica, stir and heat it to 140°C, introduce nitrogen and pressurize it to 6MPa, heat it to 220°C, rotate at 80r / min and stir for 1.5h to obtain a spinning solution;
[0056] Step A2, electrospinning the spinning solution obtained in step A1 to obtain a fiber web, and preliminarily hot-rolling the fiber web with a roller to obtain a non-woven fabric; wherein the spinning voltage is 26 kV, the spinning push speed is 0.003 mm / s, and the receiving distance is 6 cm;
[0057] Step A3, xylene ketone and acetone are mixed uniformly in a mass ratio of 1:100 to obtain an initiator solution, the non-woven fabric obtained in step A2 is soaked in the initiator solution for 20 minutes and then taken out, placed in dark conditions for 30 minutes, the modification liquid is sprayed on the non-woven fabric, and then irradiated under an ultraviolet lamp with a power of 400 W and an irradiation spectrum of 380 nm for 10 minutes. After the end, ultrasonic cleaning with acetone for 5 minutes, cleaning three times, and finally vacuum drying at 30°C to constant weight, shearing and forming, to obtain a wear-resistant and moisture-absorbing non-woven fabric lining; the amount ratio of the modification liquid to the non-woven fabric is 5mL:28g.
[0058] Wherein, the modified silicon dioxide in step A1 is prepared by the following steps:
[0059] Step S1, under nitrogen protection, add 0.1 mol of N, N'-dimethyldodecyl tertiary amine, 0.1 mol of γ-chloropropyltrimethoxysilane and 35 mL of methanol into a round-bottom flask, stir at a speed of 80 r / min for 20 min, add 0.83 g of potassium iodide, control the reaction temperature to 70°C, stir at a speed of 200 r / min for 24 h, after the reaction is completed, remove methanol from the reaction product by vacuum rotary evaporation to obtain a viscous product, dissolve the viscous product in a mixed solvent of acetone and ethanol in a volume ratio of 1:1 for recrystallization, filter, and obtain an intermediate product;
[0060] Step S2, add 7g methanol, 2g deionized water and 1g intermediate product into a round-bottom flask, stir for 8min, add acetic acid into the round-bottom flask to adjust the pH value to 4, hydrolyze at room temperature for 4h, add 11.2g nano-silica into the round-bottom flask, heat to 110°C, ultrasonically disperse at a frequency of 53kHz for 30min, centrifuge at a speed of 1500r / min for 10min, wash the precipitate with deionized water 5 times, and dry at 110°C to constant weight to obtain modified silica.
[0061] Wherein, the modified liquid in step A3 is prepared by the following steps:
[0062] Step C1, 0.1 mol of 2-vinyl-4,4-dimethyl-2-oxazolin-5-one, 41 mL of acetone, 45 mL of deionized water and 0.1 mol of trimethylammonium chloride acetohydrazide were added to a reaction kettle, stirred at a speed of 80 r / min for 8 min, then 22 mL of saturated sodium bicarbonate solution was added, and the reaction was carried out at a temperature of 37° C. for 24 h. After the reaction was completed, rotary evaporation was performed at 40° C. for 30 min, and a 20% sodium chloride solution was added for salting out, and then suction filtration was performed. The filter cake was dried at 45° C. to constant weight to obtain intermediate 1;
[0063] Step C2, add 2.4 g of intermediate 1, 4.3 g of sodium styrene sulfonate, 48 mL of anhydrous ethanol and 30 mL of deionized water into a stirring tank, stir evenly at a speed of 200 r / min to obtain a modified liquid.
[0064] Comparative Example 1
[0065] The modified silicon dioxide in Example 1 was removed, and the other raw materials and preparation process remained unchanged.
[0066] Comparative Example 2
[0067] The wear-resistant and moisture-absorbing nonwoven lining is made by the following steps:
[0068] Step A1, add 40g high-density polyethylene into a reaction kettle, heat it to 120°C, keep it warm for 10min, then add 30g difluorochloromethane and 10g modified silica, stir and heat it to 140°C, introduce nitrogen and pressurize it to 6MPa, heat it to 220°C, rotate at 80r / min and stir for 1.5h to obtain a spinning solution;
[0069] Step A2, electrospinning the spinning solution obtained in step A1 to obtain a fiber web, and preliminarily hot-rolling the fiber web with a roller to obtain a non-woven fabric; wherein the spinning voltage is 26 kV, the spinning push speed is 0.003 mm / s, and the receiving distance is 6 cm.
[0070] The preparation process of modified silicon dioxide is the same as that in Example 2.
[0071] Comparative Example 3
[0072] This comparative example is a shoe lining polypropylene nonwoven fabric produced by Dongguan Huiyu Nonwoven Technology Co., Ltd.
[0073] The nonwoven fabrics of Examples 1-3 and Comparative Examples 1-3 were subjected to performance tests, and the test standards were as follows:
[0074] Optical contact angle test: OCA15EC optical contact angle measuring instrument was used for the test. Each group of non-woven fabrics was pasted in the middle of a glass sheet with double-sided tape. The sample size was 45 mm × 6 mm.
[0075] Antibacterial performance test: Based on GB / T20944.3-2008 "Evaluation of antibacterial properties of textiles Part 3: Oscillation method", Escherichia coli and Staphylococcus aureus were selected to quantitatively test the antibacterial properties of hydrogel fibers. The antibacterial rate of the sample was calculated according to the following formula: Y = W t -Q t W t ×100% Where: Y is the antibacterial effect of the sample; W t Q is the average value of the viable bacteria concentration in the flask after 24 hours of oscillation contact with the control sample; t It is the average value of the viable bacteria concentration in the flask after 24 hours of oscillation contact with the antibacterial sample;
[0076] Wear rate: The friction and wear test was carried out using an MRH-3 ring-block friction and wear tester. The dual steel ring was made of GCr15 steel with a surface roughness of 0.1-0.2 μm. The friction and wear test conditions were load (50-300 N), speed (0.5-3 m / s), ambient temperature (25-140 ° C), dry friction, and the weight method was used to test the volume loss of the composite material. The material wear rate was calculated using the formula K = △V / (N×L), where △V is the sample volume loss, N is the test load, and L is the sliding distance. The test results are shown in Table 1:
[0077] Table 1
[0078]
[0079] It can be seen from Table 1 that the hydrophilicity, antibacterial rate and wear resistance test results of the wear-resistant moisture-absorbing non-woven fabrics of Examples 1-3 are better than those of Comparative Examples 1-3, indicating that the wear-resistant moisture-absorbing non-woven fabrics prepared by the present invention have excellent moisture absorption and sweat removal, antibacterial and wear resistance properties.
[0080] Example 4
[0081] A wear-resistant and highly comfortable plastic boot for industrial and mining use, comprising an injection-molded PVC boot and the wear-resistant and moisture-absorbing non-woven fabric lining of Example 1;
[0082] The wear-resistant and highly comfortable industrial and mining plastic boots are made by the following steps:
[0083] Polyurethane adhesive was applied to the inside of the injection-molded PVC boots, and then the wear-resistant and moisture-absorbing non-woven fabric lining of Example 1 was bonded to the inside of the PVC boots. The boots were allowed to stand at room temperature for 4 hours to obtain wear-resistant and highly comfortable industrial and mining plastic boots.
[0084] Example 5
[0085] A wear-resistant and highly comfortable plastic boot for industrial and mining use, comprising an injection-molded PVC boot and a wear-resistant, moisture-absorbing non-woven fabric lining according to Example 2;
[0086] The wear-resistant and highly comfortable industrial and mining plastic boots are made by the following steps:
[0087] Polyurethane adhesive was spot-coated on the inside of the injection-molded PVC boots, and then the wear-resistant and moisture-absorbing non-woven fabric lining of Example 2 was bonded to the inside of the PVC boots. The boots were allowed to stand at room temperature for 5 hours to obtain wear-resistant and highly comfortable industrial and mining plastic boots.
[0088] Example 6
[0089] A wear-resistant and highly comfortable plastic boot for industrial and mining use, comprising an injection-molded PVC boot and a wear-resistant and moisture-absorbing non-woven fabric lining according to Example 3;
[0090] The wear-resistant and highly comfortable industrial and mining plastic boots are made by the following steps:
[0091] The inside of the injection-molded PVC boots was spot-coated with polyurethane adhesive, and then the wear-resistant and moisture-absorbing non-woven fabric lining of Example 3 was bonded to the inside of the PVC boots. The boots were left to stand at room temperature for 6 hours to obtain wear-resistant and highly comfortable industrial and mining plastic boots.
[0092] Comparative Example 4
[0093] This comparison example is the industrial and mining boots sold by Bazhou City Dajie Electric Tools Business Department.
[0094] The performance of the mining boots of Examples 4-6 and Comparative Example 4 was tested. 40 miners were selected and divided into 4 groups. The miners in each group tried on the mining boots for 1 month. Then, the evaluation of the miners in each group was recorded. The comfort level was 1-5 points, from low to high. The wear degree of the lining of the mining boots in each group and the health of the miners' soles were observed and recorded. The test results are shown in Table 2:
[0095] Table 2
[0096] project Comfort score Lining wear degree Foot health Example 4 4.8 No wear No smelly or rotten feet Example 5 4.9 No wear No smelly or rotten feet Example 6 4.8 No wear No smelly or rotten feet Comparative Example 4 2.9 Damaged Smelly or rotten feet
[0097] It can be seen from Table 2 that the mining boots of Examples 4-6 are better than those of Comparative Example 4 in the tests of comfort, lining wear and sole health, indicating that the mining boots prepared by the present invention have good wear resistance and antibacterial properties, and can also improve the comfort of miners when used.
[0098] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
Claims
1. A wear-resistant and highly comfortable plastic boot for industrial and mining use, characterized in that: Includes injection molded PVC boots and wear-resistant, moisture-wicking non-woven lining; Among them, the wear-resistant moisture-absorbing non-woven fabric lining is made by the following steps: Step A1, adding high-density polyethylene into a reaction kettle, heating to 120°C, keeping the temperature for 10 minutes, adding difluorochloromethane and modified silica, stirring and heating to 140°C, introducing nitrogen and pressurizing to 6MPa, heating to 220°C, stirring for 1.5 hours, and obtaining a spinning solution; Step A2, electrospinning the spinning solution to obtain a fiber web, and preliminarily hot-rolling the fiber web with a roller to obtain a non-woven fabric; Step A3, mixing xylene ketone and acetone in a mass ratio of 1:100 to obtain an initiator solution, soaking the non-woven fabric obtained in step A2 in the initiator solution for 20 minutes, taking it out, standing it in the dark for 30 minutes, spraying the modification liquid on the non-woven fabric, and then irradiating it under ultraviolet light for 5-10 minutes. After the end, ultrasonic cleaning is performed, and finally vacuum drying is performed to constant weight, and shearing is performed to obtain a wear-resistant and moisture-absorbing non-woven fabric lining.
2. The wear-resistant and highly comfortable plastic boots for industrial and mining use according to claim 1, characterized in that: In step A1, the modified silica is prepared by the following steps: Step S1, under nitrogen protection, add N,N'-dimethyldodecyl tertiary amine, γ-chloropropyltrimethoxysilane and methanol into a round-bottom flask, stir for 20 minutes, add potassium iodide, control the reaction temperature to 70°C, stir and react for 24 hours, after the reaction is completed, vacuum rotary evaporate the reaction product, recrystallize, and filter to obtain an intermediate product; Step S2, adding methanol, deionized water and the intermediate product into a round-bottom flask, stirring for 5-8 minutes, adding acetic acid into the round-bottom flask to adjust the pH value to 3-4, hydrolyzing at room temperature for 4 hours, adding nano-silica into the round-bottom flask, heating to 110°C, ultrasonically dispersing for 30 minutes, centrifuging for 10 minutes, washing the precipitate, and drying to obtain modified silica.
3. The wear-resistant and highly comfortable plastic boots for industrial and mining use according to claim 1, characterized in that: In step A1, the mass ratio of high-density polyethylene, difluorochloromethane and modified silicon dioxide is 4:3:1, and the amount ratio of the modified liquid and the non-woven fabric in step A3 is 3-5mL:25-28g.
4. The wear-resistant and highly comfortable plastic boots for industrial and mining use according to claim 1, characterized in that: The modified liquid in step A3 is prepared by the following steps: Step C1, adding 2-vinyl-4,4-dimethyl-2-oxazolin-5-one, acetone, deionized water and trimethylammonium chloride acetohydrazide into a reaction kettle, stirring for 5-8 minutes, adding saturated sodium bicarbonate solution, reacting at 37° C. for 24 hours, after the reaction is completed, rotary evaporation at 40° C. for 20-30 minutes, salting out, suction filtering, and drying to obtain intermediate 1; Step C2: Add intermediate 1, sodium styrene sulfonate, anhydrous ethanol and deionized water into a stirring tank and stir evenly to obtain a modified liquid.